Synthesis and Characterization of Ciprofloxacin-loaded Chitosan Nanoparticles for Eradication of Pseudomonas aeroginosa Biofilm - Foroogh Faridi; Nima Bahador; Saeed Shoja; Sahar Abbasi (Mazandaran University of Medical Sciences, 2023)
Background: Pseudomonas aeruginosa biofilm is one of the problems in antibiotic treatment of infections. Nanomedicines, such as chitosan (CS) can carry multiple drugs and improve the therapeutic effects of antibiotics. Objectives: This study aimed at the synthesis and characterization of ciprofloxacin-loaded chitosan nanoparticles for eradication of P. aeroginosa biofilm. Methods: Cipro-CS microparticles were prepared by ionic gelation method and their size, zeta potential, and drug release pattern were determined. MBEC and MBIC of different groups of antibiotics (ciprofloxacin, ciprofloxacin-PAβN, CS ciprofloxacin, and CS ciprofloxacin-PAβN) were performed on biofilm samples of P. aeroginosa.  Results: Ciprofloxacin loading efficiency was 35.51%, and encapsulation efficiency was 55.06%. Released ciprofloxacin from CS nanoparticles was 80% after 24 hours. Biofilm production was positive in 96.7% of the isolates while 30.1% of the samples had strong biofilm. The best result for MBIC was CS ciprofloxacin, CS ciprofloxacin-PAβN, ciprofloxacin- PAβN, and ciprofloxacin, respectively. For MBEC the result was slightly different and from the best to better CS Ciprofloxacin-PAβN, CS Ciprofloxacin, Ciprofloxacin-PAβN, and ciprofloxacin. Conclusion: Today, with increasing antibiotic resistance, there are many challenges in treating infections. Due to the role of biofilm in antibiotic resistance, researchers are looking for new antibiotics to treat infections.